Environment-friendly anticorrosive paint for ships and preparation method thereof

By using antibacterial function microspheres and abrasion-resistant function fillers in ship anticorrosive coatings, combined with polyurethane-polycamium lotion and aluminum silver slurry, the existing coatings have been solved in terms of anti-pollution and environmental protection. And more environmentally friendly anticorrosive effect.

CN119350938APending Publication Date: 2025-01-24ANHUI ZHONGTENG CHEM TECH CO LTD

Patent Information

Application Number
CN202411369957.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing ship anticorrosion coatings have environmental protection and high cost problems in preventing marine organisms from adhering, and the use of toxic coatings will lead to environmental pollution.

Method used

Use antibacterial function microspheres and wear-resistant function fillers to cooperate with each other. By mixing with polyurethane-polypholic emulsion and aluminum silver pulp, 4,4′-diulfinine diodes are used as a curing agent to prepare an environmentally friendly ship for anticorrosive corrosion coating.

Benefits of technology

It improves the anti -pollution resistance and environmental protection of anticorrosive coatings, enhances the weather resistance and self -repair effect of coatings, and reduces the risk of marine life adhesion and reproduction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an environment-friendly anticorrosive coating for ships and a preparation method thereof, and belongs to the technical field of anticorrosive coatings. The preparation method comprises the following steps: mixing 2-ethylhexyl acrylate, methyl methacrylate, allyl polyethyoxyl sulfonate, n-hexadecane, alkyl polyoxyethylene ether and deionized water, adding a polyurethane-polyurea emulsion, antibacterial functional microspheres, a wear-resistant functional filler and aluminum paste, stirring and dispersing, and adding ammonium persulfate for polymerization reaction to obtain a polyurethane-polyurea-acrylic emulsion; and finally, mixing a curing agent to obtain the environment-friendly anticorrosive paint for ships. The anticorrosive paint is a water-based paint, and is more environment-friendly and safer compared with a paint using an organic solvent; the antibacterial functional microspheres take urea-formaldehyde resin as a shell, so that the antibacterial functional microspheres have better compatibility with the anticorrosive paint; baicalin is free of pollution to the marine environment, has a broad-spectrum antibacterial effect, and is beneficial to inhibition of initial growth of fouling organisms, reduction of attachment and reproduction of the fouling organisms on the surface of a ship and reduction of the risk of biological fouling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to an environmentally friendly anti-corrosion coating for ships and a preparation method thereof. Background Art

[0002] Ships are in the marine environment all year round. There are a large number of fouling organisms such as large algae, barnacles and shells in the ocean. The fouling of marine organisms can cause great harm to ships. These organisms can accumulate and grow on the surface of ships. Biological fouling can corrode metal and concrete, affecting the normal functions of the ship such as speed and service life.

[0003] In the past, the problem of marine organism attachment was generally solved by using toxic coatings, and tributyltin was commonly used, but it would cause serious environmental pollution and has been avoided; low surface energy coatings were also used to make it difficult for marine organisms to attach to the surface of the ship, or bio-skin was used on the surface of the ship, but the cost of use was too high. Therefore, it is particularly important to improve the environmental protection of anti-corrosion coatings while improving their anti-fouling function. Summary of the invention

[0004] The purpose of the present invention is to provide an environmentally friendly anti-corrosion coating for ships and a preparation method thereof, and to improve the anti-fouling performance of the anti-corrosion coating by cooperating with antibacterial functional microspheres and wear-resistant functional fillers.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an environmentally friendly anti-corrosion coating for ships comprises the following steps:

[0007] Step 1: Add aminopropyl-terminated polydimethylsiloxane with a molecular weight of 2000 and isophorone diisocyanate into a reactor, stir for 20-30 minutes at 80-85°C, nitrogen protection and 200-300r / min, stir and mix N-methylpyrrolidone, dihydroxymethylbutyric acid and dibutyltin dilaurate as a catalyst, add them into the reactor, continue stirring and reacting for 160-180 minutes to obtain an isocyanate-terminated prepolymer, then add 7-amino-4-methylcoumarin into the reactor and stir and react for 50-60 minutes, then dissolve 4,4′-dithiodiphenylamine in acetone and add it into the reactor, stir and react at 70-75°C for 50-60 minutes, add isooctyl acrylate and stir and react for 100-120 minutes, then neutralize with triethylamine and react for 30 minutes, add deionized water and stir and emulsify at 10000-12000r / min to obtain a polyurethane-polyurea emulsion.

[0008] Step 2: Add isooctyl acrylate, methyl methacrylate, allyl polyethoxy sulfonate, n-hexadecane, alkyl polyoxyethylene ether and deionized water into a reactor, stir at 500-800 r / min for 10-15 min, then add polyurethane-polyurea emulsion, antibacterial functional microspheres, wear-resistant functional filler and aluminum silver paste, continue stirring for 10-15 min and then ultrasonically disperse for 5-10 min, finally add ammonium persulfate and polymerize at 80-85° C. for 160-180 min to obtain polyurethane-polyurea-acrylic emulsion.

[0009] Step 3: Add the polyurethane-polyurea-acrylic emulsion into the reaction kettle, stir and mix the 4,4′-dithiodiphenylamine and anhydrous ethanol, add them into the reaction kettle, stir and mix them evenly, and obtain an environmentally friendly anti-corrosion coating for ships.

[0010] Furthermore, the dosage ratio of aminopropyl-terminated polydimethylsiloxane, isophorone diisocyanate, N-methylpyrrolidone, dihydroxymethylbutyric acid, dibutyltin dilaurate, 7-amino-4-methylcoumarin, 4,4′-dithiodiphenylamine, acetone, isooctyl acrylate, triethylamine and deionized water is 20g:10g:5mL:2.5g:0.05g:1.05g:0.79g:1mL:2.2g:1.8g:15-20mL.

[0011] Furthermore, the dosage ratio of isooctyl acrylate, methyl methacrylate, allyl polyethoxy sulfonate, n-hexadecane, alkyl polyoxyethylene ether, deionized water, polyurethane-polyurea emulsion, antibacterial functional microspheres, wear-resistant functional filler, aluminum silver paste and ammonium persulfate is 11g: 5-5.5g: 0.05g: 1-1.2g: 0.5-0.8g: 5-8mL: 30-33g: 0.1-0.15g: 2.5-3g: 0.1-0.5g: 0.25-0.28g.

[0012] Furthermore, the usage ratio of the polyurethane-polyurea-acrylic emulsion, 4,4′-dithiodiphenylamine and anhydrous ethanol is 30 g: 1.1-1.2 g: 3 mL.

[0013] Furthermore, the antibacterial functional microspheres are prepared by the following steps:

[0014] Step 1: adding sodium dodecyl sulfate and deionized water as an emulsifier into a reaction kettle, stirring and mixing, then adding baicalin, stirring and emulsifying at 55-60° C. and 1200-1500 r / min for 45-60 minutes to obtain a baicalin emulsion in an oil-in-water form;

[0015] Step 2: Add a 37% formaldehyde aqueous solution and urea into a reaction kettle, stir and mix, adjust the pH value to 7.8-8.2 with triethanolamine, then add polyvinyl alcohol, stir for 60-80 minutes at 80-85° C. and 500-600 r / min to obtain a urea-formaldehyde prepolymer dispersion;

[0016] Step 3: At a stirring speed of 200-300 r / min, add the baicalin emulsion dropwise into the urea-formaldehyde prepolymer dispersion. After the addition is completed, adjust the pH value to 2.2-2.5 with citric acid, then add sodium chloride and nano-silicon dioxide, continue stirring for 2-2.5 hours, let stand at 20-25°C for 24 hours, filter, wash the filter cake with anhydrous ethanol and deionized water for 3-5 times respectively, and vacuum dry to obtain antibacterial functional microspheres with urea-formaldehyde resin as the shell.

[0017] Furthermore, the usage ratio of sodium dodecyl sulfate, deionized water and baicalin is 2.2-2.4 g: 230-250 mL: 1.1-1.2 g.

[0018] Furthermore, the dosage ratio of the formaldehyde aqueous solution, urea and polyvinyl alcohol is 16-16.5g:10g:0.1g.

[0019] Furthermore, the usage ratio of baicalin emulsion, urea-formaldehyde prepolymer dispersion, sodium chloride and nano-silicon dioxide is 230-250g: 14-16g: 1.25-1.3g: 1.25-1.3g.

[0020] Furthermore, the wear-resistant functional filler is prepared by the following steps:

[0021] Step a: adding carbon fiber powder and mixed acid into a reactor at a mass ratio of 1:3-5, stirring at 200-300r / min for 3-4h, wherein the mixed acid is a mixture of 95% sulfuric acid and 67% nitric acid at a volume ratio of 3:1, filtering, and washing the filter cake with deionized water until the last washing liquid is neutral, thereby obtaining carboxylated carbon fiber powder;

[0022] Step b: adding carboxylated carbon fiber powder, isopropanol, deionized water and 25% ammonia water into a reaction kettle, stirring and mixing, and then ultrasonically dispersing for 5-10 minutes, then adding tetraethyl orthosilicate, stirring and reacting at 45-50° C. and 200-300 r / min for 16-18 hours, filtering, washing the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum drying, and crushing to obtain a wear-resistant functional filler;

[0023] Furthermore, the usage ratio of carboxylated carbon fiber powder, isopropyl alcohol, deionized water, ammonia water and tetraethyl orthosilicate is 1g:30-36g:10-12g:2g:5g.

[0024] Beneficial effects of the present invention:

[0025] The present invention prepares a polyurethane-polyurea emulsion containing a large number of carbamate groups and urea groups by reacting monomers such as aminopropyl-terminated polydimethylsiloxane and isophorone diisocyanate, and then reacts with acrylate monomers to prepare a polyurethane-polyurea-acrylic emulsion. After mixing antibacterial functional microspheres, wear-resistant functional fillers and aluminum silver paste, 4,4'-dithiodiphenylamine is used as a curing agent to obtain an environmentally friendly anti-corrosion coating for ships; the anti-corrosion coating is a water-based coating, which is more environmentally friendly and safer than coatings using organic solvents. 4,4'-dithiodiphenylamine contains disulfide bonds, and the breaking and bonding of the disulfide bonds can drive the rearrangement of the coating polymer network, showing an excellent self-repairing effect.

[0026] Aluminum paste can enhance the visual effect of the coating and improve the weather resistance of the anti-corrosion coating; the antibacterial functional microspheres use urea-formaldehyde resin as the shell, which has better compatibility with the anti-corrosion coating and helps to improve its dispersibility and durability; baicalin is non-polluting to the marine environment and has a broad-spectrum antibacterial effect, which helps to inhibit the initial growth of fouling organisms, reduce the attachment and reproduction of fouling organisms on the surface of ships, and reduce the risk of biological fouling; baicalin, as a flavonoid substance, can be adsorbed on the metal surface through its carbon-carbon bond, carbon-oxygen bond and carbon-carbon double bond after release, and its hydroxyl group can be oxidized to carbonyl, which reduces the oxidation of metal ions through reduction, and helps to improve the anti-corrosion performance of the anti-corrosion coating; the wear-resistant functional filler uses carbon fiber powder as the matrix and is coated with nano-silicon dioxide on the surface, which helps to improve the hardness, adhesion and impact resistance of the anti-corrosion coating. The introduction of wear-resistant functional fillers increases the roughness and surface free energy of the coating surface, thereby improving the wettability and surface free energy of the coating, and helps to prevent marine microorganisms from attaching and growing on the coating surface. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1: A method for preparing an environmentally friendly anti-corrosion coating for ships, comprising the following steps:

[0029] S1: Add 16 kg of 37% formaldehyde aqueous solution and 10 kg of urea into a reactor, stir and mix, adjust the pH value to 7.8 with triethanolamine, then add 0.1 kg of polyvinyl alcohol, stir for 60 min at 80°C and 500 r / min to obtain a urea-formaldehyde prepolymer dispersion; add 2.2 kg of sodium dodecyl sulfate as an emulsifier and 230 L of deionized water into a reactor, stir and mix, then add 1.1 kg of baicalin, stir and emulsify for 45 min at 55°C and 1200 r / min to obtain a baicalin emulsion in an oil-in-water form.

[0030] S2: At a stirring speed of 200 r / min, add 230 kg of baicalin emulsion into 14 kg of urea-formaldehyde prepolymer dispersion. After the addition is completed, adjust the pH value to 2.2 with citric acid, then add 1.25 kg of sodium chloride and 1.25 kg of nano-silicon dioxide, continue stirring for 2 h, let stand at 20 ° C for 24 h, filter, wash the filter cake with anhydrous ethanol and deionized water for 3 times respectively, and vacuum dry to obtain antibacterial functional microspheres with urea-formaldehyde resin as the shell.

[0031] S3: Add carbon fiber powder and mixed acid into the reactor in a mass ratio of 1:3, stir at 200r / min for 3h, the mixed acid is a mixture of 95% sulfuric acid with a mass fraction of 95% and 67% nitric acid with a volume ratio of 3:1, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and obtain carboxylated carbon fiber powder.

[0032] S4: 10 kg of carboxylated carbon fiber powder, 300 kg of isopropanol, 100 kg of deionized water and 20 kg of 25% ammonia water were added into a reactor, stirred and mixed, and then ultrasonically dispersed for 5 minutes. Then, 50 kg of tetraethyl orthosilicate was added, and the reaction was stirred at 45°C and 200 r / min for 16 hours. The filter cake was washed twice with deionized water and anhydrous ethanol respectively, vacuum dried, and crushed to obtain a wear-resistant functional filler.

[0033] S5: 20 kg of aminopropyl-terminated polydimethylsiloxane with a molecular weight of 2000 and 10 kg of isophorone diisocyanate were added to the reactor, and stirred for 20 min at 80 ° C, nitrogen protection and 200 r / min. 5 L of N-methylpyrrolidone, 2.5 kg of dihydroxymethylbutyric acid and 0.05 kg of dibutyltin dilaurate as a catalyst were stirred and mixed and added to the reactor. The stirring reaction was continued for 160 min to obtain an isocyanate-terminated prepolymer. Then, 1.05 kg of 7-amino-4-methylcoumarin was added to the reactor and stirred for 50 min. Then, 0.79 kg of 4,4′-dithiodiphenylamine was dissolved in 1L acetone and added into the reactor, stirred and reacted at 70°C for 50min, 2.2kg isooctyl acrylate was added and stirred and reacted for 100min, then neutralized with 1.8kg triethylamine and reacted for 30min, 15L deionized water was added and stirred at 10000r / min for emulsification to obtain a polyurethane-polyurea emulsion.

[0034] S6: 11 kg of isooctyl acrylate, 5 kg of methyl methacrylate, 0.05 kg of allyl polyethoxy sulfonate, 1 kg of n-hexadecane, 0.5 kg of alkyl polyoxyethylene ether and 5 L of deionized water were added into the reactor, stirred at 500 r / min for 10 min, and then 30 kg of polyurethane-polyurea emulsion, 0.1 kg of antibacterial functional microspheres, 2.5 kg of wear-resistant functional filler and 0.1 kg of aluminum silver paste were added. After stirring for 10 min, ultrasonic dispersion was carried out for 5 min, and finally 0.25 kg of ammonium persulfate was added and polymerized at 80 ° C for 160 min to obtain polyurethane-polyurea-acrylic emulsion.

[0035] S7: Add 30 kg of polyurethane-polyurea-acrylic emulsion into the reactor, stir and mix 1.1 kg of 4,4′-dithiodiphenylamine and 3 L of anhydrous ethanol, add them into the reactor, stir and mix evenly, and obtain an environmentally friendly anti-corrosion coating for ships.

[0036] Embodiment 2: A method for preparing an environmentally friendly anti-corrosion coating for ships, comprising the following steps:

[0037] S1: Add 16.2 kg of 37% formaldehyde aqueous solution and 10 kg of urea into a reactor, stir and mix, adjust the pH value to 8 with triethanolamine, then add 0.1 kg of polyvinyl alcohol, stir for 70 min at 82° C. and 550 r / min to obtain a urea-formaldehyde prepolymer dispersion; add 2.3 kg of sodium dodecyl sulfate as an emulsifier and 240 L of deionized water into a reactor, stir and mix, then add 1.15 kg of baicalin, stir and emulsify for 50 min at 58° C. and 1350 r / min to obtain a baicalin emulsion in an oil-in-water form.

[0038] S2: At a stirring speed of 250r / min, add 240kg of baicalin emulsion into 15kg of urea-formaldehyde prepolymer dispersion. After the addition is completed, adjust the pH value to 2.3 with citric acid, add 1.28kg of sodium chloride and 1.28kg of nano-silicon dioxide, continue stirring for 2.2h, let stand at 23℃ for 24h, filter, wash the filter cake with anhydrous ethanol and deionized water for 4 times respectively, and vacuum dry to obtain antibacterial functional microspheres with urea-formaldehyde resin as the shell.

[0039] S3: Add carbon fiber powder and mixed acid into the reactor in a mass ratio of 1:4, stir at 250r / min for 3.5h, the mixed acid is a mixture of 95% sulfuric acid with a mass fraction and 67% nitric acid with a volume ratio of 3:1, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and obtain carboxylated carbon fiber powder.

[0040] S4: 10 kg of carboxylated carbon fiber powder, 330 kg of isopropanol, 110 kg of deionized water and 20 kg of 25% ammonia water were added into a reactor, stirred and mixed, and then ultrasonically dispersed for 8 minutes. Then, 50 kg of tetraethyl orthosilicate was added, and the reaction was stirred at 48 ° C and 250 r / min for 17 hours. After suction filtration, the filter cake was washed twice with deionized water and anhydrous ethanol respectively, vacuum dried, and crushed to obtain a wear-resistant functional filler.

[0041] S5: 20 kg of aminopropyl-terminated polydimethylsiloxane with a molecular weight of 2000 and 10 kg of isophorone diisocyanate were added to the reactor, and stirred for 25 min at 82 ° C, nitrogen protection and 250 r / min. 5 L of N-methylpyrrolidone, 2.5 kg of dihydroxymethylbutyric acid and 0.05 kg of dibutyltin dilaurate as a catalyst were stirred and mixed and added to the reactor. The stirring reaction was continued for 170 min to obtain an isocyanate-terminated prepolymer. Then, 1.05 kg of 7-amino-4-methylcoumarin was added to the reactor and stirred for 55 min. Then, 0.79 kg of 4,4′-dithiodiphenylamine was dissolved in 1L acetone and added into the reactor. The mixture was stirred at 72°C for 55 minutes. 2.2kg isooctyl acrylate was added and stirred for 110 minutes. Then 1.8kg triethylamine was used for neutralization and reaction for 30 minutes. 18L deionized water was added and stirred at 11000r / min for emulsification to obtain a polyurethane-polyurea emulsion.

[0042] S6: 11 kg of isooctyl acrylate, 5.2 kg of methyl methacrylate, 0.05 kg of allyl polyethoxy sulfonate, 1.1 kg of n-hexadecane, 0.65 kg of alkyl polyoxyethylene ether and 6 L of deionized water were added into the reactor, stirred at 600 r / min for 12 min, and then 32 kg of polyurethane-polyurea emulsion, 0.12 kg of antibacterial functional microspheres, 2.8 kg of wear-resistant functional filler and 0.3 kg of aluminum silver paste were added. The stirring was continued for 12 min and then ultrasonically dispersed for 8 min. Finally, 0.26 kg of ammonium persulfate was added and polymerized at 82 ° C for 170 min to obtain polyurethane-polyurea-acrylic emulsion.

[0043] S7: Add 30 kg of polyurethane-polyurea-acrylic emulsion into the reactor, stir and mix 1.15 kg of 4,4′-dithiodiphenylamine and 3 L of anhydrous ethanol, add them into the reactor, stir and mix evenly, and obtain an environmentally friendly anti-corrosion coating for ships.

[0044] Embodiment 3: A method for preparing an environmentally friendly anti-corrosion coating for ships, comprising the following steps:

[0045] S1: Add 16.5 kg of 37% formaldehyde aqueous solution and 10 kg of urea into a reactor, stir and mix, adjust the pH value to 8.2 with triethanolamine, then add 0.1 kg of polyvinyl alcohol, stir for 80 min at 85°C and 600 r / min to obtain a urea-formaldehyde prepolymer dispersion; add 2.4 kg of sodium dodecyl sulfate as an emulsifier and 250 L of deionized water into a reactor, stir and mix, then add 1.2 kg of baicalin, stir and emulsify for 60 min at 60°C and 1500 r / min to obtain a baicalin emulsion in an oil-in-water form.

[0046] S2: At a stirring speed of 300 r / min, 250 kg of baicalin emulsion was added dropwise to 16 kg of urea-formaldehyde prepolymer dispersion. After the addition was completed, the pH value was adjusted to 2.5 with citric acid, and then 1.3 kg of sodium chloride and 1.3 kg of nano-silicon dioxide were added. The mixture was stirred for 2.5 h, allowed to stand at 25 °C for 24 h, and filtered. The filter cake was washed 5 times with anhydrous ethanol and deionized water respectively, and vacuum dried to obtain antibacterial functional microspheres with urea-formaldehyde resin as the shell.

[0047] S3: Add carbon fiber powder and mixed acid into the reactor at a mass ratio of 1:5, stir at 300r / min for 4h, the mixed acid is a mixture of 95% sulfuric acid with a mass fraction and 67% nitric acid with a volume ratio of 3:1, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and obtain carboxylated carbon fiber powder.

[0048] S4: Add 10kg of carboxylated carbon fiber powder, 360kg of isopropanol, 120kg of deionized water and 20kg of 25% ammonia water into a reactor, stir and mix, and then ultrasonically disperse for 10 minutes. Then add 50kg of tetraethyl orthosilicate, stir and react at 50°C and 300r / min for 18 hours, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, vacuum dry, and crush to obtain a wear-resistant functional filler.

[0049] S5: 20 kg of aminopropyl-terminated polydimethylsiloxane with a molecular weight of 2000 and 10 kg of isophorone diisocyanate were added to the reactor, and stirred for 30 min at 85 ° C, nitrogen protection and 300 r / min. 5 L of N-methylpyrrolidone, 2.5 kg of dihydroxymethylbutyric acid and 0.05 kg of dibutyltin dilaurate as a catalyst were stirred and mixed and added to the reactor. The stirring reaction was continued for 180 min to obtain an isocyanate-terminated prepolymer. Then, 1.05 kg of 7-amino-4-methylcoumarin was added to the reactor and stirred for 60 min. Then, 0.79 kg of 4,4′-dithiodiphenylamine was dissolved in 1L acetone and added into the reactor. The mixture was stirred at 75°C for 60min. 2.2kg isooctyl acrylate was added and stirred for 120min. Then 1.8kg triethylamine was used for neutralization and reaction for 30min. 20L deionized water was added and stirred at 12000r / min for emulsification to obtain a polyurethane-polyurea emulsion.

[0050] S6: 11 kg of isooctyl acrylate, 5.5 kg of methyl methacrylate, 0.05 kg of allyl polyethoxy sulfonate, 1.2 kg of n-hexadecane, 0.8 kg of alkyl polyoxyethylene ether and 8 L of deionized water were added into the reactor, stirred at 800 r / min for 15 min, and then 33 kg of polyurethane-polyurea emulsion, 0.15 kg of antibacterial functional microspheres, 3 kg of wear-resistant functional filler and 0.5 kg of aluminum silver paste were added. After stirring for 15 min, ultrasonic dispersion was performed for 10 min, and finally 0.28 kg of ammonium persulfate was added and polymerized at 85 ° C for 180 min to obtain polyurethane-polyurea-acrylic emulsion.

[0051] S7: Add 30 kg of polyurethane-polyurea-acrylic emulsion into the reactor, stir and mix 1.2 kg of 4,4′-dithiodiphenylamine and 3 L of anhydrous ethanol, add them into the reactor, stir and mix evenly, and obtain an environmentally friendly anti-corrosion coating for ships.

[0052] Comparative Example 1: Based on Example 3, no antibacterial functional microspheres were added, and the other steps remained unchanged to prepare an anti-corrosion coating.

[0053] Comparative Example 2: Based on Example 3, no wear-resistant functional filler was added, and the other steps remained unchanged to prepare an anti-corrosion coating.

[0054] Comparative Example 3: Based on Example 3, the wear-resistant functional filler was replaced with carbon fiber powder of the same mass, and the other steps remained unchanged to prepare an anti-corrosion coating.

[0055] Performance tests were conducted on Examples 1 to 3 and Comparative Examples 1 to 3. Tinplate was used as a substrate. The surface was polished evenly and then washed with anhydrous ethanol, dried, coated with different anticorrosive coatings and cured into a coating with a thickness of 0.2 mm to prepare different samples. The hardness of different coatings was tested with reference to GB / T6739-2009, the adhesion of different coatings was tested with reference to GB / T 9286-2021, the impact resistance of different coatings was tested with reference to GB / T 1732-2020, and an antifouling performance test with a cycle of 12 months was conducted at Lianyungang Port with reference to GB / T5370-2007 to observe the biological fouling area on the surface of the sample. A salt spray resistance test was conducted with reference to GB / T 1771-2007.

[0056] The results are shown in Table 1:

[0057] Table 1

[0058] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Pencil hardness (H) 4 4 4 4 2 3 Adhesion grade 3 3 3 3 2 2 Impact strength(cm) 50 50 50 50 30 40 Biofouling area (%) 9.2 9.7 9.4 15.2 13.6 10.5 Salt spray resistance (1000h) No change No change No change A small amount of bubbles There are a lot of bubbles There are a lot of bubbles

[0059] As can be seen from Table 1, the anticorrosive coatings in Examples 1 to 3 have better salt spray resistance, better anticorrosion effect, higher pencil hardness, higher adhesion level and impact strength, and smaller biological fouling area. Comparative Example 1 shows that antibacterial functional microspheres help reduce the fouling area and salt spray resistance at elevated temperatures, and Comparative Examples 2 and 3 show that wear-resistant functional fillers help improve the pencil hardness, adhesion level and impact strength of the coating, and carbon fiber powder coated with nano-silicon dioxide has a better protective effect on the attachment of marine organisms.

[0060] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an environmentally friendly anti-corrosion coating for ships, characterized in that: The steps include: Step 1: Add aminopropyl-terminated polydimethylsiloxane with a molecular weight of 2000 and isophorone diisocyanate to a reactor, stir for 20-30 minutes at 80-85°C, nitrogen protection and 200-300 r / min, stir and mix N-methylpyrrolidone, dihydroxymethylbutyric acid and dibutyltin dilaurate, add to the reactor and continue stirring and reacting for 160-180 minutes, then add 7-amino-4-methylcoumarin to the reactor and stir and react for 50-60 minutes, then dissolve 4,4′-dithiodiphenylamine in acetone and add to the reactor, stir and react for 50-60 minutes at 70-75°C, add isooctyl acrylate and stir and react for 100-120 minutes, neutralize with triethylamine and react for 30 minutes, add deionized water and stir and emulsify at 10000-12000 r / min to obtain a polyurethane-polyurea emulsion; Step 2: Add isooctyl acrylate, methyl methacrylate, allyl polyethoxy sulfonate, n-hexadecane, alkyl polyoxyethylene ether and deionized water into a reactor, stir at 500-800 r / min for 10-15 min, then add polyurethane-polyurea emulsion, antibacterial functional microspheres, wear-resistant functional filler and aluminum silver paste, continue stirring for 10-15 min, then ultrasonically disperse for 5-10 min, finally add ammonium persulfate and perform polymerization at 80-85° C. for 160-180 min to obtain polyurethane-polyurea-acrylic emulsion; Step 3: Add the polyurethane-polyurea-acrylic emulsion into the reaction kettle, stir and mix the 4,4′-dithiodiphenylamine and anhydrous ethanol, add them into the reaction kettle, stir and mix them evenly, and obtain an environmentally friendly anti-corrosion coating for ships.

2. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 1, characterized in that: The amount ratio of the aminopropyl-terminated polydimethylsiloxane, isophorone diisocyanate, N-methylpyrrolidone, dihydroxymethylbutyric acid, dibutyltin dilaurate, 7-amino-4-methylcoumarin, 4,4′-dithiodiphenylamine, acetone, isooctyl acrylate, triethylamine and deionized water is 20g:10g:5mL:2.5g:0.05g:1.05g:0.79g:1mL:2.2g:1.8g:15-20mL.

3. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 1, characterized in that: The dosage ratio of isooctyl acrylate, methyl methacrylate, allyl polyethoxy sulfonate, n-hexadecane, alkyl polyoxyethylene ether, deionized water, polyurethane-polyurea emulsion, antibacterial functional microspheres, wear-resistant functional filler, aluminum silver paste and ammonium persulfate is 11g: 5-5.5g: 0.05g: 1-1.2g: 0.5-0.8g: 5-8mL: 30-33g: 0.1-0.15g: 2.5-3g: 0.1-0.5g: 0.25-0.28g.

4. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 1, characterized in that: The usage ratio of the polyurethane-polyurea-acrylic acid emulsion, 4,4'-dithiodiphenylamine and anhydrous ethanol is 30g:1.1-1.2g:3mL.

5. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 1, characterized in that: The antibacterial functional microspheres are prepared by the following steps: At a stirring speed of 200-300 r / min, the baicalin emulsion is added dropwise to the urea-formaldehyde prepolymer dispersion, the pH value is adjusted to 2.2-2.5 with citric acid, sodium chloride and nano-silicon dioxide are added, stirring is continued for 2-2.5 hours, and the mixture is allowed to stand at 20-25° C. for 24 hours, filtered, the filter cake is washed, and vacuum dried to obtain antibacterial functional microspheres with urea-formaldehyde resin as the shell; The usage ratio of the baicalin emulsion, the urea-formaldehyde prepolymer dispersion, the sodium chloride and the nano-silicon dioxide is 230-250 g: 14-16 g: 1.25-1.3 g: 1.25-1.3 g.

6. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 5, characterized in that: The preparation method of the baicalin emulsion is as follows: sodium dodecyl sulfate and deionized water are added into a reaction kettle and stirred and mixed, then baicalin is added, and emulsification is stirred at 55-60° C. and 1200-1500 r / min for 45-60 min to obtain a baicalin emulsion in an oil-in-water form; The dosage ratio of the sodium dodecyl sulfate, deionized water and baicalin is 2.2-2.4 g: 230-250 mL: 1.1-1.2 g.

7. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 5, characterized in that: The preparation method of the urea-formaldehyde prepolymer dispersion is as follows: adding 37 wt % formaldehyde aqueous solution and urea into a reaction kettle, stirring and mixing, adjusting the pH value to 7.8-8.2 with triethanolamine, adding polyvinyl alcohol, stirring at 80-85° C. and 500-600 r / min for 60-80 min, and obtaining a urea-formaldehyde prepolymer dispersion; The dosage ratio of the formaldehyde aqueous solution, urea and polyvinyl alcohol is 16-16.5g:10g:0.1g.

8. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 1, characterized in that: The wear-resistant functional filler is prepared by the following steps: Add carboxylated carbon fiber powder, isopropanol, deionized water and 25 wt% ammonia water into a reaction kettle, stir and mix, and then ultrasonically disperse for 5-10 minutes, add tetraethyl orthosilicate, stir and react at 45-50° C. and 200-300 r / min for 16-18 hours, filter, wash the filter cake, vacuum dry, and crush to obtain a wear-resistant functional filler; The usage ratio of the carboxylated carbon fiber powder, isopropanol, deionized water, ammonia water and tetraethyl orthosilicate is 1g:30-36g:10-12g:2g:5g.

9. The method for preparing an environmentally friendly anti-corrosion coating for ships according to claim 8, characterized in that: The preparation method of the carboxylated carbon fiber powder is as follows: The carbon fiber powder and the mixed acid are added into the reactor in a mass ratio of 1:3-5, and stirred at 200-300r / min for 3-4h. The mixed acid is a mixture of 95% sulfuric acid with a mass fraction and 67% nitric acid with a volume ratio of 3:

1. The mixture is filtered and the filter cake is washed with deionized water until the last washing liquid is neutral to obtain carboxylated carbon fiber powder.

10. An environmentally friendly anti-corrosion coating for ships, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anticorrosion and antifouling integrated self-repairing microcapsule and preparation method thereof

    CN111925681A

  • Modified acrylic emulsion and preparation method thereof

    CN114085330A

  • Anti-corrosion coating for fan blade and preparation method of anti-corrosion coating

    CN115109506A

  • Self-repairing hyperbranched waterborne polyurethane as well as preparation method and application thereof

    CN115124679A

  • Preparation method of disulfide bond-containing high-strength self-repairing organic silicon modified polyurea marine antifouling coating

    CN117820949A

Cited By

  • Hydrophilic modified polyurethane-polydimethylsiloxane anti-biofouling coating and preparation method thereof

    CN120775487A

  • Organic silicon side chain modified acrylate polymer antifouling coating and preparation method thereof

    CN122405135A